Content Study Of 7th-Grade Science Textbooks Using An Esd Viewpoint On Living Things And Their Surroundings - Ismail Ismail; Diana Rochintaniawati; Anna Permanasari; Riandi Riandi (Ta'dib, 2022)
Textbooks function as one the useful teaching materials in the curriculum. The purpose of the study was to identify the content of Education for Sustainable Development (ESD) in science textbooks for grade 7 junior high school semester 2 particularly the subject of living things and their environment consisting of socio-cultural, environmental, and economic aspects that met the textbook evaluation criteria. Data were collected by analyzing seven junior high school textbooks used in Jambi. The research instrument is a text analysis check sheet based on ESD indicators containing socio-cultural, environmental, and economic perspectives. The study discovered that teachers learn from textbooks that promote an ESD viewpoint on each subject that takes into account socio-cultural, environmental, and economic factors. The examination of the seven teaching resources revealed that the integration of the information in the teaching resources from the ESD perspective has to be revised to address the growing environmental issues. The second semester of the 2013 curriculum saw the introduction of the ESD perspective on scientific teaching materials in the form of textbooks for the 7th grade SMP. These textbooks included elements of ESD but still kept them distinct from one another. The environmental dimension is the most prominent feature of ESD in the scientific textbooks for the second semester of the 7th- grade curriculum in 2013.